Local broadcast journalists: level of job perception in their workplace / Siti Zabedah Mohd Shariff - Mohd Shariff, Siti Zabedah (Faculty of Communication and Media Studies (FCMS), 2008)
The level of commitment in reporting the news by broadcast journalists in the local TV stations namely in RTM1 of Radio Television Malaysia, a government station and two private TV stations, TV3 and ntv7 depends on their professional roles, attitudes a behaviour that are influenced by the culture of their workplace. The notion of whether these individuals have their journalistic autonomy in news reporting is also based on the working environment in the different TV newsrooms they are working in.